Roberto Matta’s Hallucinations: poetry and space - Hosiasson, Laura Janina (Literatura e Sociedade, 2012)
From the examination of two documents, a film-documentaryand a collection of interviews, these notes try to approach to thefigure of Roberto Matta and his Poetics, pointing out possiblecompositional relationships between Painting and Poetry.